The Effect of Endorphine Massage Againt Decrease in Pregnant Womens Back Pain in Varastri Salon Day Spa Sleman Yogyakarta - Casnuri, Casnuri; Sulastri, Ani (Universitas Respati Yogyakarta, 2020)
Pregnancy is something that is happy for every couple. But sometimes complaints arise during pregnancy. Complaints that often arise in pregnant women are back pain. Back pain usually occurs in trimester II and trimester III. Back pain can be treated with non-pharmacological therapy. Non pharmacological therapy can be done with Endorphine massage techniques. Endorphine massage can be done by health workers and non health workers. But many health workers, especially midwives who have not done endorphin massage, including in DIY. Action midwives who often do when pregnant women complain of back pain is to provide counseling on how to relieve pain. So that pregnant women do not know the benefits of Endorphin massage. The purpose of this study was to determine the effect of endorphine massage on reducing back pain in pregnant women at Varastri Salon Day Spa Sleman Yogyakarta. The research method uses experimental design with the pretest and posttest one group pre experimental design approach. Data collection was carried out on April 4 to May 6 2019 at Varastri Salon Day Spa Sleman Yogyakarta in samples that met the inclusion criteria of 30 people. Samples were taken by acidental sampling technique. Instrument by questionnaire and data analysis using the Wilcoxon test. The results showed that the back pain of pregnant women before endorphin massage (pretest), mild pain category was 53.3% and moderate pain 46.7%. Back pain in pregnant women after endorphin massage (post test), mild pain category 96.7% and moderate pain 3.3%. Statistical test results show that there is an effect of endorphin massage on the decrease in back pain of pregnant women (p-value: 0.000).